Double endoscopic bypass for gastric outlet obstruction and biliary obstruction - Brewer Gutierrez, Olaya I.; Nieto, Jose; Irani, Shayan; James, Theodore; Pieratti Bueno, Renata; Chen, Yen-I; Bukhari, Majidah; Sanaei, Omid; Kumbhari, Vivek; Singh, Vikesh K.; Ngamruengphong, Saowanee; Baron, Todd H.; Khashab, Mouen A. (Endoscopy International Open, 2017)
Background and study aims Double endoscopic bypass entails EUS-guided gastroenterostomy (EUS-GE) and EUS-guided biliary drainage (EUS-BD) in patients who present with gastric outlet and biliary obstruction. We report a multicenter experience with double endoscopic bypass.Patients and methods Retrospective, multicenter series involving 3 US centers. Patients who underwent double endoscopic bypass for malignant gastric and biliary obstruction from 1/2015 to 12/2016 were included. Primary outcome was clinical success defined as tolerance of oral intake and resolution of cholestasis. Secondary outcomes included technical success, re-interventions and adverse events (AE).Results Seven patients with pancreatic head cancer (57.1 % females; mean age 64.6 ± 12.5 years) underwent double endoscopic bypass. Four patients had EUS-GE and EUS-BD performed during the same session with a mean procedure time of 70 ± 20.4 minutes. EUS-GE and EUS-BD were technically successful in all patients, all of whom were able to tolerate oral intake with resolution of cholestasis in 6 (87.5 %). One patient had a repeat EUS-BD with normalization of bilirubin. There were no adverse events. Conclusions Double endoscopic bypass is feasible and effective when performed by experienced operators. Studies comparing this novel concept to existing techniques are warranted.